Bulk Metallic Glasses and Their Composites: A Brief History of Diverging Fields. (10th January 2013) - Hofmann, Douglas C.
Abstract : Bulk metallic glasses (BMGs) and their derivative metal matrix composites (BMGMCs) are emerging high-performance engineering materials that are on the precipice of widespread commercialization. This review article discusses the origin of these materials and how their applications and research focus have divided into two distinct fields, one primarily focused on the plastic-like processability of BMGs and the other on the enhanced fracture mechanics of BMGMCs. Although the materials are of similar composition and origin, it is argued that their implementation will be widely varying due to their different processing requirements and intended uses. BMGs will likely find use as plastic-replacement components in cosmetic applications (e.g., watches, cell phones, biomedical implants) while BMGMCs will be used in structural applications (e.g., golf clubs, hardware for defense, energy absorbing structures).